2017
DOI: 10.1002/oby.21945
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Peripheral Adipokines and Inflammation Markers: A Systematic Review and Meta-Analysis

Abstract: This is the first quantitative synthesis of human studies on the association between circulating adipokines and inflammation biomarkers. Potential influence of age on these associations requires further evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 40 publications
0
43
0
Order By: Relevance
“…When linking obesity and inflammatory processes in IBD, adipokines are of particular interest. In several pathological states, the strong correlation between adipokine levels and inflammation severity is demonstrated [57,90,[129][130][131] (Figure 3). However, the results of the discussed studies are contradictory, as there is still no consensus on the exact role they play in the pathogenesis and course of IBD.…”
Section: Adipokinesmentioning
confidence: 91%
“…When linking obesity and inflammatory processes in IBD, adipokines are of particular interest. In several pathological states, the strong correlation between adipokine levels and inflammation severity is demonstrated [57,90,[129][130][131] (Figure 3). However, the results of the discussed studies are contradictory, as there is still no consensus on the exact role they play in the pathogenesis and course of IBD.…”
Section: Adipokinesmentioning
confidence: 91%
“…The most studied biomarkers include C-reactive protein (CRP), interleukin-6 (IL-6), interleukin-10 (IL-10), tumor necrosis factor alpha (TNF-alpha). Data from a meta-analysis investigating potential relationships between the adipose tissue-derived cytokines leptin and adiponectin and inflammatory biomarkers including CRP, IL-6, and TNF-alpha suggested a positive correlation between leptin and all three inflammatory biomarkers, whereas there was a negative correlation with respect to adiponectin and the biomarkers [31]. When adjusted for age, Grassman et al observed that correlations weakened as the age of the participants increased.…”
Section: Gender-specific Differences In Aging Due To Inflammationmentioning
confidence: 99%
“…Furthermore, inflammatory biomarkers as high‐sensitivity C‐reactive protein (hs‐CRP) and TNF‐α seem also to be risk factors for both type 2 diabetes and CVDs (Bellou, Belbasis, Tzoulaki, & Evangelou, ; Singh, Morris, Smith, Moxon, & Golledge, ). Their plasma level is usually inversely associated to adiponectin level and directly to the leptin one (Graßmann, Wirsching, Eichelmann, & Aleksandrova, ).…”
Section: Introductionmentioning
confidence: 99%